Didactics of Social Studies in Initial Teacher Training in Primary Education: The Case of the University of Costa Rica - Escobar Escamilla, Wilman (2024)
The present article deals with the conceptual, methodological and evaluation elements related to the didactics of social studies, from the international and local levels. These elements serve as a reference to analyze aspects of the initial teacher training of the Bachelor and Bachelor’s Degree in Elementary Education at the University of Costa Rica, Rodrigo Facio Campus. The aim is to analyze this initial training, determining its approach to the trends in the specific field of Social Studies teaching. To achieve this objective, a mapping of the course programs and the bibliographic analysis of the specific didactics mentioned above are used. It is concluded that there is an important approach of the programmatic proposal of the Elementary Education program of the University of Costa Rica, finding that there are courses that seek a teacher training that allows facing classroom challenges, promoting innovation, and leaving aside traditional teaching models. This does not imply the absence of opportunities for improvement in initial university training in the field of social studies didactics.